PILIHAN SENGKETA EKONOMI SYARIAH: KONSEP MELALUI LITIGASI Dan NON LITIGASI - hendrianto hendrianto (Al-Amwal : Journal of Islamic Economic Law, 2021)
This study aims to reveal the comparative norms of sharia economic dispute resolution through litigation and non-litigation, both in terms of settlement time, costs, procedures, settlement institutions, enforcement of rights, and justice.research (Library Library Research Research) Thisuses documentation data collection techniques with data analysis, namely comparative analysis. The results showed that both litigation and non-litigation attempt to apply legal justice in resolving cases. While the differences exist in terms of the relatively long settlement time through litigation, the cost of cases through litigation is relatively expensive, procedures through formal litigation while informal non-litigation, there is only one litigation settlement institution, namely the court, while non-litigation has more variations in deliberation, consultation, mediation, conciliation or assessment of experts and arbitrator, litigation is the enforcement of rights, while non-litigation is not, and through litigation feels less justice, while non-litigation prioritizes the agreement of both parties.